Inovasi Fermentasi: Meningkatkan Kandungan Antioksidan pada Bekatul Menggunakan Aspergillus Oryzae - Hafidh Al Azzhar; Mardiyono Mardiyono; Hery Muhamad Ansory (Fakultas Farmasi Universitas Setia Budi, 2023)
This study aims to assess the antioxidant activity of fermented rice bran extract as an innovative approach to enhance the content of bioactive compounds. Although rice bran is known for its richness in phenolic compounds and γ-oryzanol, the use of enzymatic fermentation to increase its bioactivity remains limited. The research explores the antioxidant activity of fermented rice bran extract, providing fresh insights into harnessing the untapped potential of natural antioxidants. Rice bran was fermented with Aspergillus oryzae for 7, 14, and 21 days. The fermented product was then extracted using 70% ethanol, and its antioxidant activity was determined in vitro using the DPPH method. The results indicated that a 14-day fermentation exhibited the highest antioxidant activity (AAI 1.47), categorized as strong antioxidant activity. For non-fermented rice bran and 7-day fermentation, AAI values were 1.09 and 1.05, respectively. Fermentation for 21 days showed the lowest antioxidant activity (AAI 0.55), which was categorized as moderate. These findings contribute to understanding the impact of fermentation duration on the antioxidant activity of rice bran, supporting its potential as a valuable source of antioxidants.